Rewards For Deeds According to the Claims In East Aceh Regency - Ibnu Mukti; Achyar Zaen (Program Pascasarjana UIN Sumatera Utara Medan, 2018)
This study aims to know the concept of reward practice to others according to mazahibul ar-ba'ah, the proposed reward deeds of deeds to others, the legal basis of reward practice according to scholars in the district of East Aceh. This study uses a qualitative method. The process of collecting data is done by field study. In analyzing the data the researcher uses qualitative analysis technique with the steps of data exposure, observation, interview, documentation, and conclusion. The results of the study found that: (1) The concept of rewarding the deeds to others according to the mazahib al ar-ba'ah that the Hanafi scholars that sending the reward of recitation of the Qur'an to the legal deceased is allowed. While Imam Malik asserted, that awarding the reward of charity to the legitimate law is prohibited and the reward is not up and does not benefit the dead. The famous opinion of Imam As-Shafi'i that he did not forbid grant recitation of the Qur'an to the dead and will arrive. While in the Bahali madhhab, there are two opinions. Some religious clerics allow and some forbid. (2) The proposition of reward of deeds to others is Surah al-Hashr verse 10. In the hadith narrated by Abu Hurairah (3) The opinion of ulama in the District of East Aceh against the reward of reward of practice to others that may and will be up to fahala to others, even in practice there are some practices that have been done by the people of East Aceh when there are people who died, including tahlil, read Al-Qur'an, alms, badal hajj, until there are most people who give kafarah and fidiyah well it is for prayer or for fasting that is not done and does not have time to diqadha while still alive. This is done by the people of East Aceh Regency, becoming a habit when there are people who die because they believe they will increase the reward to others with fatwas and explanations from the scholars in the local District.